The Role of Project-Based Learning through Narrative Writing in Enhancing Students’ Motivation to Practice Writing in English: A Case Study at SMAN 6 Karawang - Jaya Indra; Fela Dafitri (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Students’ motivation to write in English as a foreign language (EFL) classroom is often limited by difficulties in vocabulary, grammar, idea development, and text organization. To address this issue, Project-Based Learning (PjBL) integrated with digital tools can be used to create more engaging and meaningful writing activities. This study was conducted at SMAN 6 Karawang and involved twelve eleventh-grade students who participated in a narrative writing project. This study employed a qualitative case study design, with data collected through open-ended questionnaires, classroom observations, teacher feedback, and students’ narrative writing projects. n the project, Padlet was used to support students’ narrative writing, sharing, and feedback activities, while Canva was used to design the poster or cover as the visual product of the project. The findings show that the integration of PjBL with digital tools increased students’ motivation to practice writing in English. The most significant motivational changes experienced by students were increased confidence in expressing ideas, greater enjoyment in writing activities, stronger creativity through visual design, and higher willingness to revise their writing after receiving feedback. Canva helped students design visual posters or covers related to their narrative projects, while Padlet encouraged writing practice, interaction, appreciation, and timely feedback from the teacher and peers. Although some students faced technical challenges, especially those with limited digital design skills, the overall learning process helped students become more engaged, autonomous, and motivated to write. Therefore, this study suggests that technology-integrated PjBL can support students’ motivation in EFL narrative writing by combining creativity, collaboration, and meaningful feedback.